THE EFFECT OF COMPENSATION ON JOB SATISFACTION WITH WORK MOTIVATION AS AN INTERVENING VARIABLE (Case Study at PT. Tiga Mutiara Nusantara Molding Section in Dolok Merawan District) - Eka Mayastika Sinaga; Christin Natalia Sianipar; Ranti Dwi Putri Saragih (CV. Radja Publika, 2023)
Based on the results of research and discussion regarding the effect of compensation on job satisfaction with work motivation as an intervening variable